Macro and micro effects of recent and potential shocks to copper mining in Zambia - Lofgren, Hans; Robinson, Sherman; Thurlow, James (International Food Policy Research Institute, 2002)
As a result of Zambia's dependence on copper mining, both the falling world copper price and the possible withdrawal of investment from the mining sector might seriously threaten economic growth and stability. Accordingly, the impact of a 20 percent reduction in world copper prices and a complete collapse of the copper mining sector are modeled using a 1995 computable general equilibrium model for Zambia. Results indicate that the fall in world copper prices will place significant pressure on non-mining exports, with much of the burden of raising foreign exchange falling on the food, beverages and tobacco, and textiles and garment sectors. However, the agricultural and agro-related industries are the most export-responsive (albeit from initially low levels) to the forced depreciation of the currency. The complete collapse of copper mining in Zambia is shown to have a substantial and negative impact on the economy. The fall in production and exports for this important sector leads to a considerable depreciation of the currency in order to fill the resulting gap in foreign earnings. In the short-run, real GDP is reduced by as much as 16 percent. Although the largest increase in exports arises within the food, beverages and tobacco sector, the agricultural and agro-related sectors show considerable potential as sources of foreign exchange earnings. It is found that both the fall in world prices and the reduction in mining output lead to a fall in total real household consumption. However, given that rural households derive a relatively high share of their income from tradable sectors that benefit from the depreciation, the shocks lead to a progressive redistribution of household incomes and consumption. The impact of providing an injection of foreign exchange into the country is found to involve a trade-off between alleviating the negative welfare effects of the copper mining shocks and the provision of incentives for structural adjustment. Furthermore, targeted capital investment in highly export-responsive sectors reduces the necessary depreciation of the real exchange rate, and the need for structural adjustment in other areas of the economy. -- Authors' Abstract.